Social Innovation and Empowerment in Waste Management in Jelekong, Bandung Regency - Rahman, Rafa’na; Kedua, Anggi Putra; Warman, Annisa Reinelia; Balgis, Balgis; Rambe, Erwin Syahputra; A’yuni, Luthfiya; Santoso, Rahmawati; Naufal, Vieri Muhammad; Maesaroh, Wina Siti; Yuliar, Sonny (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
Waste management challenges have continued to evolve in tandem with rapid population growth, which directly contributes to increasing volumes of waste. This study investigates the innovation transition in waste management practices at PUSPA Jelekong, located in Bandung Regency, Indonesia. Employing a descriptive qualitative approach, the research draws on primary data (observations and interviews) as well as secondary sources (literature and regulatory documents). The analysis is framed using Frank Geels’ Multi-Level Perspective (MLP), which conceptualizes sociotechnical transitions across three analytical levels: niches, regimes, and landscapes. The study delineates three key phases of transition: prior to 2019, the period between 2019 and 2022, and from 2023 onward. The findings reveal a substantial transformation in PUSPA Jelekong’s waste management system from a previously inadequate framework to a more integrated and innovative model. The MLP framework proves instrumental in identifying stable landscape pressures, cross-level actor interactions, and critical factors driving the transition. Moreover, the process reflects a broader shift in the social function of waste. Through PUSPA’s educational initiatives, waste has been increasingly a shift toward practices that may support the development of a community-based circular economy.